Coherent movement patterns of female northern elephant seals across the NE Pacific Ocean - Pei, Shichao; Zhang, Xiangliang; Eguíluz, Víctor M.; Kienle, Sarah S.; Robinson, Patrick W.; Costa, Daniel P.; Duarte, Carlos M. (Frontiers in Marine Science, 2023)
Northern elephant seals engage in large-scale foraging migrations traveling up to 15,000 Km over 8 months in the northeast Pacific. While traditionally considered solitary migrants, we demonstrate here that female seals migrate in a surprisingly coherent manner, for individual northern elephant seals traveling in over such a large region of the ocean. Animal movement remained coherent, in terms of the direction of individual swimming relative to group movement, throughout much of their migrations. Movement coherence remained well above the value expected if the movement was independent until the migrating seals were further than 1,000 Km from the colony, beyond which movement coherence declined. Migrating seals presented regional aggregations consisting of female seals traveling within the center of the aggregation, closely following the main migration pathway, with individuals isolated on the extremes of the aggregation. These formations were preserved in the out-and-return migration trips. Animals at the edges of the group show an absence of correlation in their movement with the rest of animals. The observed movements exhibited a lag in the group movement patterns that was greater for female animals > 1,000 Km apart. A model that reproduced movement based on the average individual movement properties failed to reproduce the observed movement patterns. In turn, when a parameter was introduced that reflected group behavior, the resulting modelled movement conformed to the observed patterns, thereby demonstrating the presence of coherent, or synchronized, movement. Whereas the duration of female migration is ultimately constrained by reproductive biology, the coherent movement may involve both endogenous and exogenous cues determining the timing of the initiation of return across 25 million Km2 in the northeast Pacific.